(untitled) (Jurnal Ilmiah Pertanian Nasional, 2026)
Maize is an important food crop in Indonesia as a major source of carbohydrates. Cultivation techniques involving the determination of optimal plant spacing and a balanced application of organic and inorganic fertilizers are expected to enhance crop productivity. The regulation of plant spacing and the balance between organic and inorganic fertilization in maize cultivation need to be implemented to evaluate appropriate spacing arrangements and fertilizer dosages in order to achieve optimal maize growth and yield. The field experiment was conducted from October to December 2024 in Sumberjo Village, Sutojayan District, Blitar Regency, at an altitude of 137 m above sea level (lowland), with an average temperature of 23°C to 28°C. The study employed a two-factor randomized complete block design (RCBD) with three replications. The first factor was plant spacing, consisting of 100x20 cm (J1), 75x20 cm (J2), and 50x20 cm (J3). The second factor was organic-inorganic fertilization, including 700 kg ha⁻¹ of manure without NPK (P1), 700 kg ha⁻¹ of manure combined with 350 kg ha⁻¹ of NPK (P2), and 350 kg ha⁻¹ of NPK (P3). Observed variables included ear length, ear weight with husk, ear weight without husk, grain weight per plant, plant height, leaf area, and number of leaves. The collected data were analyzed using analysis of variance (ANOVA), and when significant differences were detected, the analysis was followed by the Least Significant Difference (LSD) test at the 5% significance level. The plant spacing treatments and fertilization combinations showed no significant interaction for any of the observed variables. Plant spacing had no significant effect on either growth or yield variables of maize. In contrast, the combination of 700 kg ha⁻¹ of manure and 350 kg ha⁻¹ of NPK fertilizer had a significant effect on all observed variables. Based on these findings, sustainable maize cultivation is recommended to apply balanced fertilization consisting of 700 kg ha⁻¹ of manure and 350 kg ha⁻¹ of NPK fertilizer. Jagung termasuk bahan pangan penting di Indonesia sebagai penyedia sumber karbohidrat. Teknik bertanam melalui penentuan jarak tanam optimal dan keseimbangan pupuk organik anorganik diharapkan meningkatkan produksi tanaman. Pengaturan jarak tanam serta keseimbangan antara pemupukan organik dan anorganik pada tanaman jagung perlu diterapkan untuk mengkaji ukuran jarak tanam dan dosis pupuk organik-anorganik yang tepat sehingga menghasilkan pertumbuhan dan hasil jagung yang optimal. Percobaan lahan pada bulan Oktober sampai Desember 2024 di Desa Sumberjo Kec. Sutojayan Kabupaten Blitar yang terletak pada ketinggian 137 m dpl (dataran rendah), suhu 23℃ sampai 28℃. Rancangan penelitian yang digunakan adalah rancangan acak kelompok lengkap (RAKL) dua faktor, pengulangan sebanyak tiga kali. Faktor pertama perlakuan ukuran jarak tanam, terdiri atas: 100×20 cm (J1), 75×20 cm (J2), dan 50×20 cm (J3), sedangkan factor lainnya adalah pemupukan organik-anorganik meliputi pupuk kandang 700 kg ha-1 tanpa NPK (P1), pupuk kandang 700 kg/ha dan NPK 350 kg ha-1(P2), dan 350 kg ha-1 pupuk kandang + NPK 350 kg ha-1 (P3). Variabel pengamatan meliputi panjang tongkol. Bobot tongkol dengan kelobot, bobot tongkol tanpa kelobot, berat biji per tanaman, tinggi tanaman, luas daun, dan jumlah daun. Data hasil pengmatan dianalisis menggunakan analisis sidik ragam, dan dilanjutkan dengan uji Beda Nyata Terkecil (BNT) pada taraf 5% apabila hasil signifikan. Perlakuan jarak tanam dan kombinasi pemupukan tidak menunjukkan interaksi yang nyata pada semua variabel pengamatan. Perlakuan jarak tanam tidak memperlihatkan pengaruh yang signifikan secara nyata baik pada variabel pertumbuhan maupun hasil jagung. Kombinasi pupuk kandang 700 kg ha-1 dan NPK 350 kg ha-1 berpengaruh signifikan terhadap semua variabel yang diamati. Berdasarkan penelitian tersebut, dalam budidaya tanaman jagung berkelanjutan direkomendasikan dengan pemupukan berimbang yaitu pupuk kandang sebesar 700 kg ha-1 dan NPK sebesar 350 kg ha-1.